Prospective Clinical Trial for Septic Arthritis: Cartilage Degradation and Inflammation Are Associated with Upregulation of Cartilage Metabolites - Hagen Schmal; Anke Bernstein; Matthias J. Feucht; Benjamin Erdle; Jan M. Pestka; That Minh Pham; Eva Johanna Kubosch (Mediators of Inflammation)
Background. Intra-articular infections can rapidly lead to osteoarthritic degradation. The aim of this clinical biomarker analysis was to investigate the influence of inflammation on cartilage destruction and metabolism. Methods. Patients with acute joint infections were enrolled in a prospective clinical trial and the cytokine composition of effusions (n=76) was analyzed. Characteristics of epidemiology and disease severity were correlated with levels of cytokines with known roles in cartilage turnover and degradation. Results. Higher synovial IL-1β concentrations were associated with clinical parameters indicating a higher disease severity (p<0.03) excluding the incidence of sepsis. Additionally, intra-articular IL-1β levels correlated with inflammatory serum parameters as leucocyte counts (LC) and C-reactive protein concentrations (p<0.05) but not with age or comorbidity. Both higher LC and synovial IL-1β levels were associated with increased intra-articular collagen type II cleavage products (C2C) indicating cartilage degradation. Joints with preinfectious lesions had higher C2C levels. Intra-articular inflammation led to increased concentrations of typical cartilage metabolites as bFGF, BMP-2, and BMP-7. Infections with Staphylococcus species induced higher IL-1β expression but less cartilage destruction than other bacteria. Conclusion. Articular infections have bacteria-specific implications on cartilage metabolism. Collagen type II cleavage products reliably mark destruction, which is associated with upregulation of typical cartilage turnover cytokines. This trial is registered with DRKS00003536, MISSinG.